The thickening web of Asian security cooperation deepening defense ties among U.S. allies and partners in the Indo-Pacific - Harold, Scott 1975-; Grossman, Derek; Harding, Brian; Hornung, Jeffrey; Poling, Gregory B.; Smith, Jeffrey; Smith, Meagan L. (RAND Corporation, 2019)
Key U.S. allies, security partners, and diplomatic interlocutors in the Indo-Pacific have been establishing or deepening their defense ties by branching out, engaging with each other on high-level security consultations, selling or transferring defense articles, engaging in joint defense industrial development, carrying out bilateral training and exercises, and signing defense-related agreements. Today these nations are also cooperating with non-U.S.-treaty countries such as India, Indonesia, and Vietnam that have aligned themselves more closely with the United States as China has grown both more powerful and more assertive in recent years. As a consequence, a set of important new linkages and security commitments among regional actors is forming, with substantial consequences for the United States, China, and the Indo-Pacific region. This report highlights the extent to which regional actors' security initiatives are a response to the perceived threat posed by a rising, assertive China; it calls attention to the strong support that the United States continues to enjoy across the region, with numerous actors expanding their security partnerships out of a desire to reinforce the existing regional order centered on a set of U.S. alliances so as to help share the burdens of security maintenance. The analysis points out the importance of understanding the diverse motivations regional actors have for expanding and deepening their regional security partnerships and highlights key areas for building partner capacity. Finally, the authors clarify which aspects of deepening security relationships derive from concerns about China and which stem from considerations other than balancing
"RAND International Security and Defense Policy Center, National Security Research Division ."
"Prepared for the MacArthur Foundation."
Keywords: Geopolitik; Internationale Kooperation; USA; Indopazifik; Security, International / Indo-Pacific Region; Geopolitics / Indo-Pacific Region; International cooperation; Indo-Pacific Region / Strategic aspects; Indo-Pacific Region / Foreign relations / United States; United States / Foreign relations / Indo-Pacific Region; Indo-Pacific Region / Foreign relations / China; China / Foreign relations / Indo-Pacific Region; Diplomatic relations; Geopolitics; Security, International; Strategic aspects of individual places; China; Indo-Pacific Region; United States